Talking About Barriers to Disease-Modifying Anti-Rheumatic Drugs: Content Analysis of Audio-Recorded Routine Clinical Visits of Patients with Rheumatoid Arthritis - Voshaar MJH; Van den Bemt BJ; van de Laar MA; van Dulmen S; Vriezekolk JE (Patient Preference and Adherence)
Marieke JH Voshaar,1,2 Bart JF Van den Bemt,1– 3 Mart A van de Laar,4 Sandra van Dulmen,5,6 Johanna E Vriezekolk3 1Radboud University Medical Center, Department of Pharmacy, Nijmegen, the Netherlands; 2Sint Maartenskliniek, Department of Pharmacy, Nijmegen, the Netherlands; 3Sint Maartenskliniek, Department of Research, Nijmegen, the Netherlands; 4University of Twente, Faculty of Behavioral, Management and Social Sciences, Enschede, the Netherlands; 5Nivel (Netherlands Institute for Health Services Research), Utrecht, the Netherlands; 6Radboud University Medical Center, Department of Primary and Community Care, Nijmegen, the NetherlandsCorrespondence: Marieke JH Voshaar, Radboud University, Department of Pharmacy, Postbus  9102.  6500 HC, Nijmegen, the Netherlands, Email Marieke.Voshaar@Radboudumc.nlPurpose: Effective healthcare professional-patient communication is essential for medication adherence. Conversations about patient’s barriers to medication use, for example, could help to enhance adherence and consequently improve treatment outcomes. However, it is unclear whether and how barriers to medication use are discussed during routine rheumatology consultations. The aims of this study were to examine 1) the barriers and facilitators to medication use raised by patients during real-life rheumatology outpatient consultations, and whether the issue of medication (non)adherence was discussed (communication content); and 2) how rheumatologists responded to the barriers (communication process).Methods: A total of 134 audio-recordings of real-life outpatient rheumatology consultations were analysed. Barriers and facilitators for the current use of disease-modifying anti-rheumatic drugs were identified and categorized using a previously adapted Theoretical Domains Framework. The way rheumatologists responded to the barriers brought up by the patients was analysed using relevant parts of the Roter Interaction Analysis System.Results: In 58 of the 134 consultations, at least one barrier or facilitator to current medication use was brought up by the patient; in 31 out of 134 consultations, medication (non)adherence was addressed. Most facilitators were related to the quality of the needles, the use of an injection pen instead of a syringe, dose reduction because of low disease activity and timing of the medication. The majority of barriers were related to experiencing side effects and doubts about efficacy and resistance of (long-term use of) medication. Rheumatologists’ responses to barriers related to disease-modifying anti-rheumatic drugs were mostly a combination of instrumental (counselling) and affective (agreement) communication.Conclusion: Barriers to current disease-modifying anti-rheumatic drugs’ use raised by patients and discussed during routine rheumatology consultations were primarily related to side effects and concerns about the efficacy and long-term use. Continuous attention of these barriers and tailored responses to patients’ concerns are key to promote better adherence to treatment.Keywords: barriers and facilitators to medication, adherence, healthcare professional-patient communication, instrumental and affective communication, outpatient visits